The strategy of the administrative sections specialized in undermining the Algerian revolution - Abdel Hadi, Hussein; moulde nnbia, karim (The Algerian Historical Journal, 2026)
Our main objective in this research is to reveal the Main issues for which the colonial authority set up at the end of September 1955 a specialized administrative apparatus, under the name: "s.a.s.", Our study examines the subject from two opposite dimensions, each dimension reveals the other dimension, the first is the declared strategy of "the sas", and the second is the revealing dimension of the truth of what the advertiser hides. It is no secret to anyone that we are facing a device that wants to be the flexible tool and at the same time the penetrating device of Algerian rural society. However, "The sas" collided with a complex reality; during our research, many paradoxes have been revealed to us.The serious issues of this device have shown us images of its management of a set of challenges.